Tax avoidance with profit management as a moderating variable; influence of profitability, leverage, company size, and related party transactions - Franky Bernando; Benny Oktaviano (Trigin Publisher, 2023)
The aims of this research is to examine and analyze the effect of Profitability, Leverage, Firm Size and Related Party Transactions on Tax Avoidance with Earnings Management as a moderating variable. The population in this study were food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2018 – 2021. The sampling technique used was purposive sampling so that a total of 176 research samples were used in this study. The data analysis technique used in this study is panel data regression and moderated regression analysis. The results of the analysis show Related Party Transactions has a significant positive effect on Tax Avoidance, Profitability, Leverage, Firm Size have no effect on Tax Avoidance. Earnings Management as a moderating variable is able to moderate the effect of Profitability, Leverage, Firm Size, and Related Party Transactions on Tax Avoidance.%MCEPASTEBIN%